Verification of an analytical method and in vitro comparative study of the dissolution kinetics of generic amoxicillin 500 mg capsules manufactured by the local pharmaceutical industry in the Democratic Republic of the Congo - Mayangi Makola, Mannix; Mbinze Kindenge, Jérémie; Mana Kialengila, Didi; Bayebila Menanzambi, Tresor; Ntambwe Ngoyi, Michel; Mankulu Kakumba, Jocelyn; Mbenza Phuati, Adelard; Nsangu Mpasi, Jean (Orapuh Journal, 2026)
IntroductionStrengthening the local pharmaceutical industry in the Democratic Republic of the Congo to produce affordable, effective, and high-quality medicines contributes to improved health outcomes and economic development. The government grants a monopoly to local manufacturers for the production of certain generic medicines, such as amoxicillin. These products are required to meet established quality, safety, and efficacy standards to adequately address population health needs.PurposeThe objective of this study was to evaluate the interchangeability of different brands of amoxicillin produced by local manufacturers in the Democratic Republic of the Congo with a reference (innovator) product through comparative in vitro dissolution testing.MethodsTwo generic products manufactured by local pharmaceutical companies and one innovator product were evaluated. For each product, one batch was randomly purchased from authorised wholesalers. Analyses were conducted using high-performance liquid chromatography in accordance with the United States Pharmacopeia–National Formulary (USP–NF, 2024). Twelve dosage units were analysed to establish dissolution profiles. Comparative dissolution testing was performed at different pH conditions (1.2, 4.5, and 6.8) using a paddle-type dissolution apparatus. Quantification was carried out by UV spectrophotometry, and dissolution profiles were compared using the difference factor (f₁) and similarity factor (f₂). Acceptable ranges were 0–15 for f₁ and 50–100 for f₂.ResultsAll samples complied with the USP–NF 2024 specifications. However, dissolution recovery rates differed across sampling points. The fit factor analysis demonstrated interchangeability with the reference product only at pH 1.2, while no similarity was observed at pH 4.5 and 6.8.ConclusionThe findings indicate potential concerns regarding the efficacy and interchangeability of locally manufactured generic amoxicillin products compared with the innovator product. Manufacturers should re-evaluate their formulations, considering all factors influencing dissolution performance. In addition, regulatory authorities should strengthen post-marketing surveillance to ensure the quality of pharmaceutical products.